Nilai-Nilai Edukatif Dalam Tradisi Ujung: Kajian Etnografi Di Masyarat Boyolali Jawa Tengah - Haryanto, Sigit (Universitas Muhammadiyah Surakarta, 2020)
Cultural values always exist in the physical form of tradition. One of the traditions that have rich of values is ujung tradition. It is annual event held by most Javanese people. It has a correlation to lebaran fitr.Â The participants of this tradition are from children to old people. Visiting their parent, relative, and neighbor are compulsory activity.Â In addition to, they also utter forgiveness each other. The objective of this study is finding the values behind ujung tradition viewed from educative point. Ethnographic study was selected to conduct the research and participant observation was used to collect the data. Then the data were analyzed by using component analysis proposed by Spradlay.The results of the study showed that there five educative values inside the ujung tradition, namely: respect, togetherness, advice, pray, and charity.From this it is understood that ujung tradition is still run well in society due to many educative values that ought to be transferred.